Assessment of the Therapeutic Potential of the Synergy of Solenostemous monostachyus and Vernonia amygdalina in Fish induced with Oxide of Calcium - Roberts Inala, Eneni; Ohwofasa Ikpesu, Thomas (Nigerian Journal of Pharmaceutical and Applied Science Research, 2022)
Background: The therapeutic capability of the synergy of Solenostemous monostachyus and Vernonia amygdalina against calcium oxide was investigated. Methods: The fish were acclimatized for fourteen days, divided into five groups, and exposing to different ranges of treatments; Group A received 250mg/L CaO; group B received 250mg/L CaO and 1500mg/L V. amygdalina; group C received 250mg/L CaO and 1500mg/L S. monstachyus; group D received 250mg/L CaO and 750mg/L each of (V. amygdalina and S. monstachyus) and the control was left untreated. Water quality were kept within normal ranges by using an aerator. The fish were removed from each aquarium on the 28th day of the experiment, blood sample was taken from the caudal vein, dissected and the brain was carefully removed, and homogenized in a bottle. The blood was centrifuged for 15 minutes to ensure that the serum was clearly separated, and was then kept at -80 °C until analysis, while the brain was centrifuged and supernatant collected in a tube and used as an enzyme source. All the markers were measured spectrophotometrically. Results: The activity of acetylcholinesterase and glutathione- s transferase were interfered in the oxide-induced fish, although it was improved when treated with each plant's extract alone, but restored in the synergy therapy. Similar observations were noticed in glucose, protein, urea, creatine, and globulin levels. Conclusion: . These findings are encouraging; nonetheless, these plant extracts should be used with caution because the abuse and misuse can be hazardous to one's health.